Di Era Covid-19 Studi Kecamatan Konda 1 Kabupaten Konawe Selatan - Imran, Muhammad; Wahid Mongkito, Abdul; Apipah Haeriah, Nur (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2022)
This study aims to find out online marketing strategies implemented before Covid-19, online marketing strategies implemented in the Covid-19 Era and online marketing strategies according to an Islamic economic perspective by Ud. Simple Kec. Konda 1 Kab. South Konawe, in the context of online marketing strategies. The urgency of this research is to provide a scientific explanation of online marketing strategies implemented before, during the Covid-19 Era and online marketing strategies according to an Islamic economic perspective by Ud. Simple Kec. Konda 1 Kab. South Conawe. This study uses descriptive qualitative methods with data collection techniques of observation, interviews and documentation. Data reduction analysis techniques, data presentation, and drawing conclusions. The results of the study can be concluded that the online marketing strategy implemented by Ud. It was simple before Covid-19, namely by using the 4P strategy, namely Promotion and Place. But since the Covid-19 outbreak, Ud. Simple experienced a very drastic decline so that the owner must improve the strategy used. Islamic economic review in the online marketing strategy carried out by Ud. Simple Kec. Konda 1 Kab. South Konawe is in accordance with the marketing strategy carried out by Rasulullah, namely Segmentation, Targeting and Positioning. And it is in accordance with the character of Islamic marketing which includes Divinity, Ethics, Realism, and Humanity. As well as not having elements that are not in accordance with Islamic law such as Tadlis, Gharar, Ba'I Najasy, Riba and Ikhtikar.